1985
DOI: 10.1111/j.1600-0447.1985.tb01261.x
|View full text |Cite
|
Sign up to set email alerts
|

Antidepressive therapy in depressed clinical suicides

Abstract: A total of 61 clinical suicides, all of them fulfilling the Research Diagnostic Criteria for a depressive disorder, were examined with regard to the psychopharmacological treatment they received at the time of their suicide. Scarcely half were treated with antidepressants, and only a small minority were optimally treated. One of the reasons for this therapeutic inadequacy lies in a discrepancy between the clinical and RDC diagnoses. An improvement in diagnostic practice, in the sense of paying more attention t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
5
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 24 publications
2
5
0
Order By: Relevance
“…The consequences are that these women are withheld from effective treatment and that the suicide risk is underestimated. It is further conspicuous that only 7% were affected by antidepressive drugs, supporting the findings of Modestin (49) and Beskow (16). Forty-three percent of those who were depressed at suicide were at some time psychiatric inpatients during the final year.…”
Section: Toxicologysupporting
confidence: 79%
“…The consequences are that these women are withheld from effective treatment and that the suicide risk is underestimated. It is further conspicuous that only 7% were affected by antidepressive drugs, supporting the findings of Modestin (49) and Beskow (16). Forty-three percent of those who were depressed at suicide were at some time psychiatric inpatients during the final year.…”
Section: Toxicologysupporting
confidence: 79%
“…These results are in accordance with the literature (Modestin, 1985): only a minority of depressed patients who committed suicide was adequately treated (21%), whereas 64% of the patients fulfilled the criteria for major depression. More recently, psychological autopsies conducted on suicide victims reported that 68% of these subjects presented with a mental disorder but none of them was in psychiatric care (Owens et al, 2003).…”
Section: Discussionsupporting
confidence: 95%
“…This is consistent with previous observation [5 1,521. Modestin (1985) [53] postulated that among treated patients who killed themselves, it was possible that treatment for depression had not been aggressive enough, as only a small minority of patients studied had optimal doses of antidepressants. In an analysis of the prevalence of physical illness in 15 studies of suicide in Western countries and Australia, Whitlock (1975) [54] found that the rate ranged from 18% to 70%; higher rates were reported in the elderly, some of whom suffered from disorders of the central nervous system and cancer.…”
Section: Discussionmentioning
confidence: 99%